EMERGING THREAT REVEALED: DIAPORTHE PARANENSIS AS THE CULPRIT BEHIND FRUIT ROT IN PEACH ORCHARDS - Greenwood, Emma Charlotte; Thomas, Noah Alexander; Johnson , Isabella Marie (Ayden Journal of Agriculture and Allied Studies, 2024)
Peach (Prunus persica) holds a significant position as the third most vital temperate fruit crop globally, following apple and pear trees. In 2019, Brazil emerged as a notable contributor to peach production, yielding 183.1 thousand tons within approximately 16 thousand hectares, with Rio Grande do Sul leading the pack at 110.2 thousand tons and São Paulo following closely with 32.9 thousand tons. However, peaches, being among the temperate fruits, possess a high susceptibility to spoilage due to their rapid post-harvest metabolism, resulting in quick loss of pulp firmness, rot, and withering. This accelerated ripening process curtails their shelf life, thus imposing substantial limitations on effective handling and transportation. Common culprits responsible for the rot of peaches include Monilinia fructicola, Penicillium, Rhizopus, Fusarium, Colletotrichum, Cladosporium, and Geotrichum. This paper delves into the challenges faced by the peach industry, focusing on the rapid deterioration of peach fruit post-harvest, and the associated incidence of rot. By analyzing the factors contributing to these issues and exploring potential solutions, this study seeks to enhance the preservation, transportation, and overall quality of peach produce.